ANALYSIS OF THE POTENTIAL AND CONTRIBUTE TO THE ENTERTAIMENT TAX ORIGINAL RECEIPT OF REGIONAL REVENUE - Dewi, Adis Berliana; Nugraha, Adri Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this research is to determine the potential of entertainment tax which is owned by Batu City and know how big contribution to the entertainment tax Local Revenue. This research used quantitative descriptive method.. The data collection techniques are interviews, observation, documentation and study of literature. This result indicate that the potential of the entertainment tax in Batu very big, but the potential was decreasing from 2012 until 2014 because entertainment tariff had been set with smaller rate. However, when viewed in terms of the potential number of visitors, it has increased every year. Based on the research there is a quite big discrepancy between realization of entertainment tax with a potential entertainment tax. This is evidenced by the percentage difference between realization and potential of the entertainment tax amounted to 58,17%. This result showed the conclusion that the potential tax revenue Entertaiment in Malang did not reflect its true potential, therefore the Department of Revenue need to optimizing Entertaiment Tax receipts of Malang for local revenue to be increased. Keywords: Potential Entertainment Tax, Entertainment Tax Contributions, Original Receipt of Regional Revenue